Microorganisms in probiotic beverage fermentation: Health benefits and mechanisms in dairy and non-dairy products - Jannah, Mirriyadhil; Wakiah, Nurul; Sandi, Olifia Mutiara; Islamawan, Praboyo Ardin; Wulan, Nur Lili Nia (Jurnal Inovasi Pangan dan Gizi, 2025)
Background: Probiotics are microorganisms that actively improve health by improving the balance of intestinal microflora when consumed alive in adequate amounts. Probiotics are directly able to help the microflora in the digestive tract to inhibit pathogenic bacteria that can interfere with the digestive tract. This review aims to find out some examples of probiotic fermented beverage products, types of microorganisms that play a role and their benefits for human health. Methods:  This article is a descriptive explanation using the literature review method. The stages of the literature review include collecting literature sources that are relevant to the research topic. Furthermore, analysis and evaluation of important findings from previous studies are carried out. Finally, a synthesis is carried out to formulate conclusions. Finding: Fermented dairy products such as yogurt, soy sauce, kefir, and yakult, as well as non-dairy products such as kombucha tea, are good sources of probiotics for health. The fermentation process in dairy products converts lactose into lactic acid, while in kombucha tea, fermentation occurs through a solution of tea and sugar with a kombucha microbial starter (a symbiosis of bacteria and yeast). Conclusion: Both fermented dairy products and non-dairy products contain probiotics that are beneficial for health. Fermentation of dairy products occurs by converting milk lactose into lactic acid. Novelty/Originality of This Study: This review uniquely compares dairy and non-dairy probiotic beverages, highlighting the symbiotic fermentation in kombucha tea as an alternative to traditional dairy products. It offers a fresh perspective on the diverse microbial mechanisms and health benefits of probiotics from both sources.